2010
DOI: 10.1111/j.1600-0609.2009.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dendritic cells in multicentric Castleman disease present human herpes virus type 8 (HHV8)‐latent nuclear antigen 1 (LANA1) in a proportion of cases and is associated with an enhanced T‐cell response

Abstract: Multicentric Castleman disease (MCD) is a rare human herpes virus type 8 (HHV8)-associated lymphoproliferative disorder that occurs more frequently in patients infected with human immunodeficiency virus (HIV). In tissue samples, HHV8-infected plasmablasts localise to the mantle zones of the lymphoid follicles. We revisited the immunohistological features in 25 lymph node (LN) and three spleen samples of MCD. In five (20%) LN and one (33%) spleen sample, HHV8 latent nuclear antigen 1 (LANA1) staining was also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The peculiar HHV‐6B immunohistochemical findings observed in our patients with benign/reactive lymphadenopathy resemble those previously described in Rosai‐Dorfman disease or sinus histiocytosis with massive lymphadenopathy, an atypical benign lymphoproliferative disorder, in which HHV‐6 antigens have been detected by immunohistochimical analyses in both histiocytes and FDCs, with a suggested pathogenetic association (Luppi et al , ). It has also been reported that EBV is able to infect and transform FDCs in vitro (Lindhout et al , ), while a HHV‐8 antigen may be presented by FDCs in multicentric Castleman disease, potentially increasing anti‐viral immune response (El‐Daly et al , ). In our cases, the possibility is raised that HHV‐6B local reactivation may indirectly modulate and trigger the proliferation of lymphocytes, by locally affecting FDCs and lymph node microenvironment (Lindhout et al , ; Luppi et al , ; Allen & Cyster, ; El‐Daly et al , ; Rezk et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peculiar HHV‐6B immunohistochemical findings observed in our patients with benign/reactive lymphadenopathy resemble those previously described in Rosai‐Dorfman disease or sinus histiocytosis with massive lymphadenopathy, an atypical benign lymphoproliferative disorder, in which HHV‐6 antigens have been detected by immunohistochimical analyses in both histiocytes and FDCs, with a suggested pathogenetic association (Luppi et al , ). It has also been reported that EBV is able to infect and transform FDCs in vitro (Lindhout et al , ), while a HHV‐8 antigen may be presented by FDCs in multicentric Castleman disease, potentially increasing anti‐viral immune response (El‐Daly et al , ). In our cases, the possibility is raised that HHV‐6B local reactivation may indirectly modulate and trigger the proliferation of lymphocytes, by locally affecting FDCs and lymph node microenvironment (Lindhout et al , ; Luppi et al , ; Allen & Cyster, ; El‐Daly et al , ; Rezk et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that EBV is able to infect and transform FDCs in vitro (Lindhout et al, 1994), while a HHV-8 antigen may be presented by FDCs in multicentric Castleman disease, potentially increasing anti-viral immune response (El-Daly et al, 2010). In our cases, the possibility is raised that HHV-6B local reactivation may indirectly modulate and trigger the proliferation of lymphocytes, by locally affecting FDCs and lymph node microenvironment (Lindhout et al, 1994;Luppi et al, 1998;Allen & Cyster, 2008;El-Daly et al, 2010;Rezk et al, 2013). However, we acknowledge that our findings do not conclusively indicate causality of HHV-6B in inducing lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmablastic cells (plasmacytoid immunoblasts) express an HHV-8-related antigen, latency-associated nuclear antigen 1 (25,26). Plasmablastic cells (plasmacytoid immunoblasts) express an HHV-8-related antigen, latency-associated nuclear antigen 1 (25,26).…”
Section: Diseases Associated With Castleman Diseasementioning
confidence: 99%
“…Small percentages of fDC from lymph node and spleen samples of MCD cases have been found to express HHV-8 LANA-1. Interestingly, these same fDC are thought to facilitate the increase of T cell infiltration into these secondary lymphoid organs (El-Daly et al, 2010). This suggests that fDC serve as functional soldiers in the DC arm of defense.…”
Section: In Hhv-8-associated Diseasementioning
confidence: 99%